Aspectos neurofisiológicos e sua relação com o acometimento clínico e funcional dos pacientes com doença pulmonar obstrutiva crônica - Rocco, Carolina Chuisoli de Miranda (2009)
Neurophysiologics alterations compromise the normal activity of the muscles, and in association with other pertinent manifestations of Chronic Obstructive Pulmonary Disease (COPD) they influence in the physical inactivity of this population. In this study, the surface electromyography was used for evaluation of the latency time of the patellar and achilles monosynaptic reflex and for evaluation of the peripheral muscular force of quadriceps muscle; the static balance was analyzed by means of the evaluation of the oscillatory center of pressure (COP) for the ground platform and the dynamic for Tinetti Scale; e finally, the functional capacity gotten by the test sit-and-up. The objective was of analysis and comparison of these neurophysiologics aspects with healthful aged and correlating them with the BODE Index. At as a moment the consequences also had been correlated with the age and height of the individuals with COPD to verify the possibility of plus a marker for the functional prognostic of this illness. The reflected latency time in the COPD meets reduction in relation to the group has controlled, as well as reduction of the peripheral muscular force and the functional capacity in the test sit-and-up. We don t find differences in relation to the evaluation of the balance. Higher BODE Index presented correlations with functional activities, Tinetti and test sit-and-up, are evidenced in individuals with lesser level of functional capacity. The alteration of the latency time of the consequence to patellar was associated with the age of COPD group, and these results can reflect as a marker functional or still prognostic, however more studies are necessary so that this objective reach the proposal desired.